(3cJGH GdcGaj aj Yde GdMSGHs - (3eMeO Hf eMeO Hf eMeO Hf GdMSf GdLPGej GdaGQbj GdeUQj, GHf fHGJg , LeGd GdOjf CHh HcQ,J (B768 (3g` s
(3ChdgG (B:s
(3Chd GdehLhO efg bhdg Edi GdeGFI hcfSHI GdeGFI Edi GdCda HGH VQH GdUMGM GYde Gf GdVQH gh JVYja CMO GdeVQhHjf s
(3BNQgG (B:s
(3aGdTF GdhGMO gh YTQhf hgh GdHYOjf XghQ GdSecI hGdfNdI GdWhjdI s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B38 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B273 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B164s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1377s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdQjGVjGJs